Sosio-Agrikultur Bali untuk Gastronomi Berkelanjutan di Indonesia - Nazrina Zuryani (Pusat Kajian Bali Universitas Udayana, 2020)
Agriculture is the foundation of sustainable gastronomy. With or without the Corona pandemy, rice-based meals such as uduk, red, campur, and tumpeng make up Indonesians’ staple food. This article analyzes how novel Balinese culinary technique enriches gastronomy and lifestyle, by blending old and new menus and thus engineering the hybrid gastronomy of the future. This research utilized qualitative explorative area of Jatiluwih and bamboo tabah cultivation in Tabanan District, Bali. Both Jatiluwih rice and bamboo tabah offer the possibility to spur culinary creativity while respecting the theory of gastronomy localisation. Typical magibung as Balinese collective eating is also a healthy moment of ethno-pedagogy for touristic purposes with local content. Regarding sustainable gastronomy in Bali, magibung with rice from Jatiluwih and tabah bamboo are topic of studies that come under the aegis “Nusantara Culinary Sociology”, a subject proposed to sociology and other students in Udayana University.